PENERAPAN MODEL PBL DIPADU MEDIA ANIMASI VIDEO UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA KONSEP SISTEM PENCERNAAN MANUSIA DI SMP NEGERI 5 BANDA ACEH - Maulina Maulina; Khairil Khairil; Safrida Safrida (Universitas Islam Negeri Ar-Raniry, 2017)
The aim of this research was to find out the implementation of Problem based learning (PBL) model which is integrated with animated video in improving students’ learning outcomes in the concept of human digestive system. The data were collected from August 16th until September 6th, 2016. An experimental method with Pretest-Posttest Control Group design was used in this research. Students of class VIII1 were chosen as experimental group, while students of class VIII2 were chosen as control group. The data were collected by using test. The data were analyzed by using independent sample – t-test with the level of significance of 0.05. The results showed that the value of t count> t table; 4,919 > 2,002 for the students’ learning outcomes. Therefore, it could be concluded that the PBL model which is integrated with animated video influenced the improvement of the students’ learning outcomes in the concept of human digestive system at SMP N 5 (State Junior High School ) Banda Aceh.